2005
DOI: 10.1212/01.wnl.0000149403.14458.7f
|View full text |Cite
|
Sign up to set email alerts
|

The role of radiotracer imaging in Parkinson disease

Abstract: Radiotracer imaging (RTI) of the nigrostriatal dopaminergic system is a widely used but controversial biomarker in Parkinson disease (PD). Here the authors review the concepts of biomarker development and the evidence to support the use of four radiotracers as biomarkers in PD: [18F]fluorodopa PET, (+)-[11C]dihydrotetrabenazine PET, [123I]beta-CIT SPECT, and [18F]fluorodeoxyglucose PET. Biomarkers used to study disease biology and facilitate drug discovery and early human trials rely on evidence that they are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
137
0
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 295 publications
(142 citation statements)
references
References 63 publications
1
137
0
4
Order By: Relevance
“…Because nigrostriatal DA deficiency characterizes PD, a variety of means to visualize abnormalities of DA uptake or storage have been developed, such as 6-[ 18 F]fluorodopa positron emission tomographic (PET) scanning [1]. The occipital cortex (OCC) contains scant dopaminergic innervation; one can quantify striatal DA deficiency from the PUT:OCC ratio of 6-[ 18 F]fluorodopa-derived radioactivity [2,3].…”
Section: Abstract or Phrasesmentioning
confidence: 99%
“…Because nigrostriatal DA deficiency characterizes PD, a variety of means to visualize abnormalities of DA uptake or storage have been developed, such as 6-[ 18 F]fluorodopa positron emission tomographic (PET) scanning [1]. The occipital cortex (OCC) contains scant dopaminergic innervation; one can quantify striatal DA deficiency from the PUT:OCC ratio of 6-[ 18 F]fluorodopa-derived radioactivity [2,3].…”
Section: Abstract or Phrasesmentioning
confidence: 99%
“…1-Methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) is a neurotoxin that induces parkinsonism in both humans [4] and non-human primates [5] with the cognitive, biochemical, histological and classical behavioral changes that occur in PD [6] . Therefore, Increasing evidence has suggested that single photon emission computed tomography (SPECT) and positron emission tomography (PET) imaging can be used to sensitively and objectively evaluate the integrity of the nigrostriatal dopaminergic system and may be useful tools for providing diagnostic information on PD [7][8][9][10] . There are numerous SPECT and PET imaging tracers for monitoring the integrity of dopaminergic neurons.…”
Section: Introductionmentioning
confidence: 99%
“…One approach has been to rely on a surrogate biomarker specific for degeneration in dopaminergic nigrostriatal projections. 18,[21][22][23]74 With use of these techniques, disease progression can apparently be inferred even when PD patients continue to receive symptomatic therapy. In each instance, the assumption is that caudate and putamen images provide a direct correlate to the number of dopaminergic projections.…”
Section: Dopaminergic Drugsmentioning
confidence: 99%
“…[21][22][23] Clinical ratings conducted after a pramipexole or levodopa washout of at least 12 hours permitted measurements of UPDRS scores in an unmedicated state. These showed no differences between the two groups; however, the short duration of washout for these symptomatic treatments is likely to have been inadequate for valid comparisons to baseline.…”
Section: Pramipexolementioning
confidence: 99%
See 1 more Smart Citation